PENGARUH INHIBITOR EKSTRAK DAUN PEPAYA TERHADAP KOROSI BAJA KARBON SCHEDULE 40 GRADE B ERW DALAM MEDIUM AIR LAUT DAN AIR TAWAR - Handani, Sri; Elta, Megi Septia (Universitas Andalas, 2012)
The inhibition effect of Carica papaya leaves exctract on the corrosion of carbon steel schedule 40 grade B ERW in fresh and sea water medium was investigated using weight loss method of monitoring a corrosion rate. The leaves were dried and ground to powder. The extract concentration used was 15%. The inhibition efficiency of 78,49% and 78,63% was obtained in fresh and sea water, respectively. The obtained results indicated that Carica papaya leaves exctract could be used as inhibitor against the corrosion of medium carbon steel in both fresh and sea water.